2012
DOI: 10.1021/jp2100057
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Degradation of Fenitrothion Insecticide and Performance of Nucleophiles: A Computational Study

Abstract: Ab initio and density functional theory (DFT) calculations have been performed to understand the destruction chemistry of an important organophosphorus insecticide O,O-dimethyl O-(3-methyl-4-nitrophenyl) phosphorothioate, fenitrothion (FN), toward nucleophilic attack. Breaking of the P-OAr linkages through nucleophilic attack is considered to be the major degradation pathway for FN. One simple nucleophile, hydroxide (OH(-)), and two different α-nucleophiles, hydroperoxide (OOH(-)) and hydroxylamine anion (NH(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…Many research groups have reported the reactivity of α‐nucleophiles toward the cleavage of carboxylate and phosphate esters in micellar media. Furthermore, the computational calculations show nucleophilic reactivity for the substrate hydrolysis . Thus, the highly efficient catalytic activity may be induced by the unshared lone pair of electron on the adjacent center of BDMO and AHA.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Many research groups have reported the reactivity of α‐nucleophiles toward the cleavage of carboxylate and phosphate esters in micellar media. Furthermore, the computational calculations show nucleophilic reactivity for the substrate hydrolysis . Thus, the highly efficient catalytic activity may be induced by the unshared lone pair of electron on the adjacent center of BDMO and AHA.…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, the computational calculations show nucleophilic reactivity for the substrate hydrolysis. [48] Thus, the highly efficient catalytic activity may be induced by the unshared lone pair of electron on the adjacent center of BDMO and AHA. It has also been observed that the nucleophilic reactivity of α-nucleophiles is much higher than that predicted by the Bronsted relationship between nucleophilicity and basicity.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…However, the formation of peroxoborates in the investigated range of pH 9-10, which is described by equations (9) and (10), is almost an undeniable fact. This approach is widely used by researchers to interpret kinetic regularities and the mechanism of oxidation in the system Н 2 О 2 /В(ОН) 3 near electrophilic centers [17,18].…”
Section: Reactivity Of Peroxoanions In the Nucleophilic Substitutimentioning
confidence: 97%
“…In addition, the reagents used in industrial technologies (alkalis, alkali metal alcohols, and amines) do not differ in their high reactivity to phosphoric and phosphonic esters [6]. The rate of decomposing MP and its analogues can be increased by the use of α-nucleophiles [8,9], the typical representative of which is the peroxide anion НОО - [10] and its derivatives -peroxoaniones [11].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…[4][5][6] In this regard, the compound O,S-dimethyl methylphosphonothiolate (DMPT) is an analogue of the chemical warfare agent, VX, due to its P-O and P-S linkages that have similar hydrolytic labilities. A number of theoretical investigations were performed for the thermal unimolecular decomposition, 18 hydrolysis, 19 and a-nucleophilic destruction 20 of such deadly agents. A number of theoretical investigations were performed for the thermal unimolecular decomposition, 18 hydrolysis, 19 and a-nucleophilic destruction 20 of such deadly agents.…”
Section: Introductionmentioning
confidence: 99%